Ngatu: A Methodological Framework for Artistic Practice - Faumuina, C (Revista GEMInIS, 2022)
This article discusses an indigenous methodological framework employed in the development of my doctoral study, ‘Asi – The Presence of the Unseen. Considering the Tongan concept of ‘asi (the unseen spirit that energises and gives agency to artistic work), the thesis asked, “What occurs when young Oceanic people work together creatively in a group, drawing on values from their cultural heritage to develop meaningful faiva (artistic performance)?” In posing this question, the study sought to understand how ‘asi might bring forward a powerful sense of belonging and co-creation that might resource artistic practice. As such, I proposed that the ‘asi identifiable at the peak of a performance, might be also be discernible before and after such an event. The methodological framework for the study drew its inspiration from approaches to making Tongan bark cloth fabric (ngatu). Given the co-creative nature of such work, the Ngatu framework positioned the investigator as both an artistic practitioner and a reflector on the practices and experiences of other people collaborating in the study.
Keywords: Belonging; Faiva; Ngatu; Oceanic; Practice-led research